8+3(s-4t)=

Simple and best practice solution for 8+3(s-4t)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 8+3(s-4t)= equation:


Simplifying
8 + 3(s + -4t) = 0
8 + (s * 3 + -4t * 3) = 0
8 + (3s + -12t) = 0

Solving
8 + 3s + -12t = 0

Solving for variable 's'.

Move all terms containing s to the left, all other terms to the right.

Add '-8' to each side of the equation.
8 + 3s + -8 + -12t = 0 + -8

Reorder the terms:
8 + -8 + 3s + -12t = 0 + -8

Combine like terms: 8 + -8 = 0
0 + 3s + -12t = 0 + -8
3s + -12t = 0 + -8

Combine like terms: 0 + -8 = -8
3s + -12t = -8

Add '12t' to each side of the equation.
3s + -12t + 12t = -8 + 12t

Combine like terms: -12t + 12t = 0
3s + 0 = -8 + 12t
3s = -8 + 12t

Divide each side by '3'.
s = -2.666666667 + 4t

Simplifying
s = -2.666666667 + 4t

See similar equations:

| -4y-3x-x=-16y | | 3y-2x^2=x | | (m-2)x^2-mx-m= | | 2(x-3)=3(x+1)-5 | | ln(9x+5)=4 | | 7y-9=2y | | 6+4x=.33(6x+9) | | 66.66666666666666666666666666666666666666666666666666666666666666666x+17=23 | | 6+4x=.33333(6x+9) | | 66.6666666666666666666666x+17=23 | | 66.6x+17=23 | | 15m-9n-6m=9n | | -51=-9x-6 | | (x-3)(5x+7)=0 | | 6=1/5(12s-6) | | .4x+10=20 | | 1/3(5y-4)=7 | | 84+y-25=180 | | 3*x^2=78 | | 36r^2-21g^2=0 | | a/6-7=-4 | | 122=(1.8XC)+32 | | 4r+2s=20 | | -5m+8m=2m+11 | | 16b^2+40bg+25g^2=0 | | 4r+25=20 | | 0.7x+17=23 | | 0.6x+17=23 | | x^2+3*y=14564 | | 0.67x+17=23 | | An=3n-7 | | 4m=4m |

Equations solver categories